Expression, location and biological effects of four and a half LIM domain protein 2 (FHL2) on granulosa cells in ovine. Issue 6 (8th April 2020) - Zhang, Limeng; Li, Runting; Chen, Longxin; Xing, Zhenzhen; Song, Yue; Nie, Xiaoning; Wang, Linqing; Han, Hongye; Liu, Aiju; Ma, Xiaofei; Ma, Runlin Z.; Tian, Shujun
Abstract: Previous studies have shown that four and a half LIM domain protein 2 (FHL2) plays an essential role in the regulation of follicular development in mammals. Although the FHL2 genes of human and mouse have been well characterized, the expression and location of FHL2 in ovary and the biological functions of FHL2 on granulosa cells (GCs) of ovine are still not clear. In this study, full‐length complementary DNA (cDNA) of FHL2 from ovine follicular GCs was amplified by real‐time PCR (RT‐PCR). The expression and location of FHL2 in ovary and GCs of ovine were studied by immunohistochemistry and immunofluorescence, and the biological effects of FHL2 on the cell proliferation, cell apoptosis, cell cycles and expression level of related genes of ovine GCs were also explored by overexpression or knockdown of FHL2. The results indicated that FHL2 was expressed in ovine follicular GCs and the sequence of the FHL2 cDNA was consistent with that predicted in GenBank, which did not cause an amino acid change. According to the results, FHL2 was expressed in ovine ovary and mainly located in the cytoplasm and nucleus of GCs. In addition, overexpression of FHL2 significantly reduced the cell viability, promoted the cell apoptosis and decreased the percentage of G0/G1 and S phase cells. RT‐PCR showed that overexpression of FHL2 significantly increased the mRNA expression level of Bax and decreased the expression of Bcl‐2 and the Bcl‐2/Bax mRNA ratio compared with the control group. Besides, the knockdown of FHL2 gene in ovine GCs significantly improved the cell viability, suppressed the cell apoptosis, decreased the mRNA expression level of Caspase‐3 gene, increased the Bcl‐2/Bax mRNA ratio and increased the percentage of S and G2/M phase cells. Our results suggest that FHL2 may play an important role in the biological functions of GCs in ovine.